Pengaruh Pemberian Ekstrak Air Buah Pepaya Muda (Carica papaya.L) terhadap Gambaran Histologi Ovarium Tikus Betina (Rattus norvegicus) - Okti Satria; Yanwirasti Yanwirasti; Anri Amir (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Papaya seed (Carica papaya L.) as antifertility has been known since 1970 can cause the quantity and quality of sperm decreased. This antifertility potency is reinforced by the existence of research showing that inside papaya seeds contain antifertility compound that is saponin. In young papaya fruit (Carica papaya L.) also contains saponins, alkaloids, minerals, vitamins, and enzymes. The latex sap from the young papaya fruit has the same influence as oxytocin on the uterus of both pregnant and non-pregnant rats (Gouado et al., 2007) this study was conducted to prove that in the water extract of young papaya fruit has antifertility effect. If this study is meaningful, it may be used as a reference for subsequent research on efforts to utilize bio-natural resources as a medicinal substance.The purpose of this study is to know the influence of young papaya fruit extract on overview of ovarium histology of female rat.This research is a quantitative research using post-test design only control group design. This research is experimental with design. The research has been conducted from November to December 2017. This research was conducted at the Regional Center of Veterinary Investigation and Testing (RSVIT) II of Bukittinggi. The population in this study was female rats with a total number of female rats during the study of 32 rats.The results showed that Fresh Papaya Fruit Extract significantly influenced the number of primary follicles and follicles of rat Atresia (Rattus novergicus) (p = 0,000).Young Pepaya Fruit Water Extract can be considered as an efficient natural contraceptive and a few side effects.